Pokolenie jutra w dzisiejszej polskiej szkole: charakterystyka, priorytety i wyzwania nie tylko w klasie językowej - Zalisz, Katarzyna (Tomorrow's school? Tradition and (r)evolutions in education, 2023)
The article will delineate the characteristics of Generation Alpha (Post-Gen-Z); children who were born after 2010, students at Polish schools today. The author will try to answer several questions related to Generation Alpha teaching environment – what the priorities and potential challenges there are, how they learn, what kind of school and teachers they need. In the article, issues such as new technologies and innovations in foreign language education as well as key competencies and XXI century skills of the Alpha students will be described.